Clinical Characterization of Patients Under 5 Years of Age Operated on For Aortic Coarctation in A Tertiary Clinic in Neiva-Huila During the Period 2018 – 2023 - Ayala Buendía, Jackeline; Hernández Gómez, Ana María; Andrea Casallas Loaiza, Nathalia; Trujillo Manzo, Alex Mauricio; Casanova, Lucia Fernanda; Laverde Gaona, Luis Alfonso (Journal of Neonatal Surgery, 2025)
Within the framework of the development of the project for the degree option of the Medicine program, of the Faculty of Health Sciences of the Navarra University Foundation – UNINAVARRA, the development of a research process was planned that would be oriented to carry out a process of clinical characterization of patients under 5 years of age operated on for aortic coarctation in a third level clinic in the city of Neiva located in the Department of Huila during the period 2018 – 2023, resulting in important findings and analyses that allow better information to be obtained for the identification of entry patterns that could significantly affect the patient's evolution during the surgical procedure and, therefore, offer statistical information that could anticipate the possible postoperative complications of patients operated on for coarctation of the aorta (CoA) and hypoplasia of the aortic arch. This information could be used to strengthen early diagnoses of the disease, provide inputs to reinforce good practices at the time of surgical intervention, and create early warnings of possible immediate and immediate postoperative complications in these patients.